Skewness preferences and asset selection: An experimental study - Tobias Bruenner; Rene Levinsky; Jianying Qiu (University of Innsbruck, Department of Public Finance, 2009)
In this paper we experimentally test skewness preferences at the individual level. Several prospects that can be ordered with respect to the third-degree stochastic dominance (3SD) criterion are ranked by the participants of the experiment. We find that the skewness of a distribution has a significant impact on the decisions. Yet, while skewness has an impact, its direction differs substantially across subjects: 39% of our subjects act in accordance with skewness seeking and 10% seem to avoid skewness. On the level of individual decisions we find that the variance of the prospects and subjects' experience increases the probability of choosing the lottery with greater skewness.
Keywords: D81; C91; G11; 330; Skewness; Stochastic dominance; Decision-making under uncertainty; Entscheidung bei Unsicherheit; Portfolio-Management; Test